1980
DOI: 10.1159/000232431
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for IgG Fc and Complement in the Mammalian Aorta

Abstract: The presence of IgG Fc receptors in the tissue sections of aorta and aortic valves of man, ox and pig was demonstrated by means of hemadsorption of human and rabbit IgG antibody sensitized erythrocytes to these sections. C3b receptors in the tissue sections of aortic valves of these three mammals were also demonstrated by using sheep erythrocytes sensitized with rabbit IgM antibody which bound murine complement. 8 of 13 systemic lupus erythematosus sera and 2 of 19 other collagen disease sera were shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The observation that the binding was abolished by treatment of tissue with cold ethanol is also consistent with the view that the adherence is caused by IgGFcR (Tonder & Thunold 1973, Kasukawa et al 1980. Free RF activity, on the other hand, can be demonstrated in sections of tissues fixed in ethanol for 18 h (Munthe & Natvig 1971, Malmstrom 1975.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The observation that the binding was abolished by treatment of tissue with cold ethanol is also consistent with the view that the adherence is caused by IgGFcR (Tonder & Thunold 1973, Kasukawa et al 1980. Free RF activity, on the other hand, can be demonstrated in sections of tissues fixed in ethanol for 18 h (Munthe & Natvig 1971, Malmstrom 1975.…”
Section: Discussionsupporting
confidence: 77%
“…Malmstrom (1975) using a similar technique reported no binding of aggregated IgG to ethanol-fixed gingival biopsy specimens. The report of Mackler et al (1978) also is at variance with the observations of several other investigators (Krogh & T0nder 1972, T0nder & Thunold 1973, Kasukawa, Okada & Igari 1980 who found that the exposure of tissues to ethanol destroys IgGFcR activity in various tissues.…”
Section: Introductionmentioning
confidence: 53%